1989
DOI: 10.1016/s0022-5347(17)40789-0
|View full text |Cite
|
Sign up to set email alerts
|

Detailed Anatomy of Penile Neurovascular Structures: Surgical Significance

Abstract: In 10 formalin-preserved adult male cadavers, dissection of the penile veins, arteries and nerves revealed information of clinical importance. The main venous drainage of the corpora cavernosa is via the cavernous veins, with additional drainage through the circumflex, deep dorsal, and crural veins. The arterial supply of the cavernous bodies varied remarkably, and the incidence of an accessory internal pudendal artery was high. The cavernous nerves, previously believed to be microscopic structures, were in fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
79
1
15

Year Published

1995
1995
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 254 publications
(101 citation statements)
references
References 24 publications
5
79
1
15
Order By: Relevance
“…The ability to recognize and quantify the nerve ®bers containing NOS is the best way to assess the integrity, pathway, degeneration or regeneration of erectile nerves. Breza and associates, 19 in cadaveric dissection, found nerve ®bers connecting the cavernous and dorsal nerves Ð a ®nding reaf®rmed by Paick et al 20 It appeared to them that the dorsal nerve serves as a`carrier' for the cavernous nerve, carrying these tiny ®bers to the distal corpora cavernosa and the glans. In the present study we found a distinct NOS staining pattern in the dorsal nerve and corpus cavernosum.…”
Section: Discussionmentioning
confidence: 93%
“…The ability to recognize and quantify the nerve ®bers containing NOS is the best way to assess the integrity, pathway, degeneration or regeneration of erectile nerves. Breza and associates, 19 in cadaveric dissection, found nerve ®bers connecting the cavernous and dorsal nerves Ð a ®nding reaf®rmed by Paick et al 20 It appeared to them that the dorsal nerve serves as a`carrier' for the cavernous nerve, carrying these tiny ®bers to the distal corpora cavernosa and the glans. In the present study we found a distinct NOS staining pattern in the dorsal nerve and corpus cavernosum.…”
Section: Discussionmentioning
confidence: 93%
“…Patient age and surgical technique, as well as possible injury to accessory pudendal arteries have all been suggested as potential explanations. 25,32,33 The results of the present physiological observations in the rat model, when taken in conjunction with the human histological data, suggest the possibility that the ancillary penile nerves are physiologically relevant and that injury to them during radical extirpative surgery may further impair penile erection. Clearly, additional study is needed to con®rm the importance of these ancillary branches of human penile nerves.…”
Section: Discussionmentioning
confidence: 57%
“…Signi®cant variation in the blood supply to the penis was found by Breza et al in a study of adult male cadavers. 12 In their dissections they found an accessory internal pudendal artery in seven of 10 cadavers, predominantly on the left. These traveled along the lower aspect of the bladder and the anterolateral surface of the prostate to the dorsal root of the penis.…”
Section: Vascular Anatomymentioning
confidence: 97%